Áreas protegidas: impactos da implementação do Parque Nacional das Sempre-Vivas (Revista Espinhaço, 2023)
The article contributes to the analysis of the effects of the implementation of the Semper-Vivas National Park (PNSV), in Alto do Jequitinhonha, in the communities of São João da Chapada, Macacos and Quartel do Indaiá. With community residents and with employees of the Chico Mendes Institute for Biodiversity Conservation (ICMBio). It was observed the difficulties of the communities since the implementation of the park, and the adaptations in face of the restrictions of the environmental legislation. In response to the impacts of the implementation of the PNSV, the increase in family farming was an alternative for income generation, in addition to being important for the food security of the residents. Regarding the distribution and spatial mobility of the population, flows to the PNSV were reduced while flows between communities were stimulated by the search for better living and working conditions. The case points to the need for studies on the impacts of the implementation of environmental protection areas on traditional populations. Documenting and understanding these transformation processes are essential for partnerships between the public sector, associations and communities, in the sense of socio-environmental planning and the construction of public policies.
Keywords: Population and environment; population in protected areas; vulnerability; Communities